Inflammatory markers in peripheral blood cells cannot predict intrauterine insemination outcome: A retrospective cohort study - Meryem Kuru Pekcan; A Seval Ozgu-Erdinc; Nafiye Yilmaz; Aytekin Tokmak; Yaprak Engin-Ustun (Wolters Kluwer Medknow Publications, 2021)
Background: Although infertility is known as a chronic inflammatory condition, the effect of the increased inflammatory response on IUI success is not clear. Systemic inflammation can be calculated by applying various hematological markers. Aims: We aimed to evaluate the ability of hematologic parameters of inflammation in predicting intrauterine insemination (IUI) outcome. Study Setting and Design: A total of 334 infertile couples included in this retrospective cohort study. The study population comprised of all couples who were candidates for ovulation induction and IUI due to polycystic ovary syndrome (PCOS) (n = 147) or unexplained infertility (UI) (n = 187). Materials and Methods: The inflammatory parameters in the complete blood count parameters, such as neutrophil-lymphocyte ratio, platelet lymphocyte ratio, platelet distribution width, plateletcrit were obtained on IUI day and compared between the two groups. The predictive values of these markers for IUI outcome were calculated. Results: There were 44 pregnancies (13.2%) in the whole study cohort. There were no significant differences between the pregnant and nonpregnant groups regarding the evaluated parameters (all P > 0.05). Also, no significant difference was observed between the patients with PCOS and UI in terms of those parameters. The area under receiver operating characteristic (ROC) curve analysis revealed that none of the inflammatory markers can predict pregnancy in intrauterine insemination cycles. Further prospective studies are needed to verify our findings. Conclusion: We found no relationship between the hematologic inflammatory markers and IUI outcome.Therefore these markers cannot be used for prediction of pregnancy.